Probing of congenital nasolacrimal duct obstruction with dacryoendoscope - Kato, Kumiko (Dove Medical Press, 2014)
BACKGROUND: A congenital nasolacrimal duct obstruction (CNLDO) is a relatively common disease in infants. We evaluated the results of probing three patients with CNLDO, under direct view, with a dacryoendoscope. METHODS: Three cases of CNLDO were examined and treated by probing with a dacryoendoscope, under intravenous anesthesia. The diameter of the dacryoendoscope probe was 0.7 mm, and we were able to observe the inner walls of the lacrimal duct and able to guide the probe through the duct. RESULTS: In all cases, the site of obstruction was detected, and the probe was used to remove the obstruction. At 2 weeks after the removal of the obstruction, there was no epiphora or mucopurulent discharge in any of the cases. No complications were detected intra- and postoperatively. CONCLUSION: Although only three cases were studied, we believe that probing with a dacryoendoscope is a safe and effective method of treating a CNLDO. More cases need to be studied.